Crystallization and physological characterization of human aquaporin 10 - Bajraktari, Niada (My University, 2012)
Integral membrane proteins control important biological processes in the cell. Being anchored to the membrane, they serve as sensors for changes in the environment in and out of the cell and they are responsible for signal transduction. They also serve as channels for the transport of ions, water and other substances and are often targets for drug development. Aquaporins are passive channels that are crucial for the survival of the cell under osmotic stress by regulating water and glycerol transport. Human aquaporin 10 (hAQP10) is an aquaglyceroporin found in the small intestine where it may be involved in the absorption of water and small nutrients. Recent studies suggest that hAqp10 might be also expressed in the stratum corneum of the skin and malfunctions of the protein might cause eczema. In this project hAQP10 was overproduced in the yeast Pichia pastoris and purified with chromatography techniques. Highly pure and concentrated protein sample was used in different crystallization setups aiming to get the three dimensional structure through X-ray diffraction. In addition, skin samples from scalpel scrapings and tape stripping were provided from a collaboration partner and analyzed with immunoblotting and immunohistochemistry. In conclusion, pre-crystal structures, spheroids, were generated having the protein in a mix of the detergents n-Dodecyl-β-D-Maltoside (DDM) and n-Octyl-β-D-Glucopyranoside (β-OG). Based on the immunoblot and the immunohistochemistry, the protein could be localized in the stratum corneum of the skin. This project lays a foundation for future work on structural studies of hAQP10 and other aquaglyceroporins.
Keywords: Biokemi och molekylärbiologi; Livsvetenskaper; Biochemistry and Molecular Biology; Life Science